2014
DOI: 10.1530/jme-14-0005
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of defective MC4R cell-surface expression and signaling by a novel pharmacoperone Ipsen 17

Abstract: Melanocortin 4 receptor (MC4R) is a key factor in regulating energy homeostasis, and null mutations occurring in the gene encoding MC4R cause severe early-onset morbid obesity in humans. Many obesity-causing mutations affecting MC4R clinically identified so far lead to failure of mutant receptors to shuttle to the plasma membrane. In this study, we show that a novel human MC4R antagonist, Ipsen 17, acted as an pharmacological chaperone of human MCR4. As tested with 12 obesity-causing human MC4R variants includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…In addition to these novel variants, previously described mutations in MC4R were found in four patients (p.R165W, c.493C>T in exon 1 in three of four, and p.V166I, c.496G>A in exon 1 in one) (15,16).…”
Section: Resultsmentioning
confidence: 82%
“…In addition to these novel variants, previously described mutations in MC4R were found in four patients (p.R165W, c.493C>T in exon 1 in three of four, and p.V166I, c.496G>A in exon 1 in one) (15,16).…”
Section: Resultsmentioning
confidence: 82%
“… 26 , 94 , 95 Recently, new MC4R antagonists, Ipsen 5i and Ipsen 17, were identified, which rescue a broader spectrum of MC4R mutants with a high efficiency at concentrations as low as 10 −9 and 10 −8 M, respectively. 96 , 97 Functionality was restored in most of the studied cases. As expected, these chaperones were unable to functionally rescue mutants with additional defects, such as impaired ligand binding ability.…”
Section: Mutations Affecting Gpcr Signalingmentioning
confidence: 73%
“…Using pharmacological chaperones for MC4R represents a possibility for the development of a targeted treatment of severe early-onset obesity caused by MC4R mutations. A study demonstrated that a novel human MC4R antagonist, Ipsen 17, serving as a pharmacological chaperone of human MC4R, increased the cell surface expression of MC4R mutants and their signaling capacity upon α-MSH stimulation [ 74 ]. Thus, using pharmacological chaperones against MC4R mutants provides an exciting disease-modifying opportunity for severe early-onset morbid obesity.…”
Section: Perspectivesmentioning
confidence: 99%